2003
DOI: 10.1053/jhep.2003.50170
|View full text |Cite
|
Sign up to set email alerts
|

Rat Hepatocyte Aquaporin–8 Water Channels Are Down–Regulated in Extrahepatic Cholestasis

Abstract: Hepatocytes express the water channel aquaporin-8 (AQP8), which is mainly localized in intracellular vesicles, and its adenosine 3 ,5 -cyclic monophosphate (cAMP)-induced translocation to the plasma membrane facilitates osmotic water movement during canalicular bile secretion. Thus, defective expression of AQP8 may be associated with secretory dysfunction of hepatocytes caused by extrahepatic cholestasis. We studied the effect of 1, 3, and 7 days of bile duct ligation (BDL) on protein expression, subcellular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 37 publications
5
69
0
Order By: Relevance
“…While T3 alone stimulated expression of AQP9 mRNA, there appeared to be no coordinate induction of protein synthesis or accumulation as a consequence of T3 stimulation. Lack of correlation between protein levels and gene expression has been well documented in several systems [23][24][25] and recently it has been shown that while bile duct ligation depressed the levels of AQP8 in rat liver, gene expression was actually enhanced [26]. These data suggest that analysis of changes in mRNA levels does not necessarily reflect or predict changes in AQP protein levels or how cell function might be altered.…”
Section: Discussionmentioning
confidence: 93%
“…While T3 alone stimulated expression of AQP9 mRNA, there appeared to be no coordinate induction of protein synthesis or accumulation as a consequence of T3 stimulation. Lack of correlation between protein levels and gene expression has been well documented in several systems [23][24][25] and recently it has been shown that while bile duct ligation depressed the levels of AQP8 in rat liver, gene expression was actually enhanced [26]. These data suggest that analysis of changes in mRNA levels does not necessarily reflect or predict changes in AQP protein levels or how cell function might be altered.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to the regulated food intake aquaporin-8 a water channel which is mainly localized in the intracellular vesicles of hepatocytes and facilitates osmotic water movement during canalicular bile secretion is downregulated. 13 Similarly the genes which play important role in the transport of lipids and cholesterol (Slc27a5 and Npc1) and oxygen (Hba-a1) are also downregulated. 14,15 The differential expression of the above genes implies that the metabolic functions in the regenerating liver are carried out at a reduced sub-optimal level at the onset of DNA synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In separate experiments, we tested the effect of UB (17.1 μM) by exposing the cells for 15 min to the pigment, previous to the incubation with tBuOOH (100 μM) for 15 min or its solvent. Cytosolic (supernatant) and total membrane (pellet)-enriched fractions were obtained by ultracentrifugation for 60 min at 100,000 × g (Carreras et al 2003) and total protein determined (Lowry et al 1951). Proteins were separated by electrophoresis on a 12%-SDS-polyacrylamide gel and after electrotransfer, nitrocellulose membranes (Immobilon-P membranes) were incubated overnight with a mouse monoclonal antibody to PKCα (BD Biosciences Pharmingen; 1:1,000).…”
Section: Assessment Of Biliary Secretion Of Bile Salts Anddinitrophenmentioning
confidence: 99%